RETRACTED: Several different ways to increase the accuracy of the numerical solution of the first order wave equation - Madaliev Murodil; Orzimatov Jahongir; Abdulkhaev Zokhidjon; Esonov Olimjon; Mirzaraximov Mirzohid (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001